Water-soluble polymeric probe with dual recognition sites for the sequential colorimetric detection of cyanide and Fe (III) ions. (August 2019) - Gupta, Moumita; Lee, Hyung-il
Abstract: A water-soluble polymeric probe derived from an azo-Schiff base was developed for the consecutive colorimetric sensing of CN − and Fe 3+ ions in water. Herein, the synthesis of a random copolymer of N, N -dimethylacrylamide (DMA) and 3-vinylbenzaldehyde (VBA) via reversible addition-fragmentation chain transfer polymerization, [p(DMA- co -VBA, P1] is described. A post-polymerization modification reaction between the aldehyde groups of P1 and (E)-2-amino-4-((4-nitrophenyl)diazenyl)phenol in ethanol led to the target polymer, P2, with azo-Schiff base moieties. The colorimetric detection of CN − ions occurred because of the abstraction of phenolic proton of P2 by the CN − ions to form hydrazone, which was accompanied by the color change from brick-red to purple. The selective colorimetric detection of Fe 3+ ions with P2 over other cations in water was also observed via the formation of a coordination complex between Fe 3+ ions and azo-Schiff base ligands of P2. After the individual detection of CN − and Fe 3+ was carried out, consecutive sensing studies were performed. Although Fe 3+ was sequentially observed after the presence of CN − ions was noted, detection using a reverse sequence from Fe 3+ to CN − was not possible because of the intense color of the resulting P2Fe 3+ complexes, which suppressed any observable color changes typically caused by the formation of hydrazone. Graphical abstract: An azo-Schiff based polymeric probe (P2) was developed for the consecutive colorimetric detection of CN − ions and Fe 3+ ions in pure aqueous media. Image 1 Highlights: Azo-Schiff-based water-soluble polymeric probe was synthesized and characterized. The probe exhibited dual detection ability towards Fe 3+ ions and CN − ions in 100% aqueous media. pH-tunable sensing of CN − ions was achieved. This probe can be used for the sequential detection of CN − ions and Fe 3+ ions.